1990
DOI: 10.1016/s0735-1097(10)80329-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of the serum magnesium concentration in patients with congestive heart failure

Abstract: Magnesium abnormalities are common in patients with congestive heart failure but the clinical and prognostic significance of an abnormal serum magnesium concentration in this disorder has not been investigated. Therefore, the relation between serum magnesium concentration and the clinical characteristics and long-term outcome of 199 patients with chronic heart failure was evaluated. The serum magnesium concentration was less than 1.6 mEq/liter in 38 patients (19%), within the normal range in 134 patients (67%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
4

Year Published

1991
1991
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 25 publications
3
65
1
4
Order By: Relevance
“…Gottlieb et al 22 investigated the association between serum Mg concentrations, clinical characteristics and longterm outcome in patients with chronic heart failure. In that study, patients with hypomagnesemia had more frequent ventricular premature complexes and episodes of ventricular tachycardia than patients with normal serum Mg concentrations.…”
Section: Association Between Ne Concentrations and Mg Dynamicsmentioning
confidence: 99%
“…Gottlieb et al 22 investigated the association between serum Mg concentrations, clinical characteristics and longterm outcome in patients with chronic heart failure. In that study, patients with hypomagnesemia had more frequent ventricular premature complexes and episodes of ventricular tachycardia than patients with normal serum Mg concentrations.…”
Section: Association Between Ne Concentrations and Mg Dynamicsmentioning
confidence: 99%
“…15 Recently, Fiset et al 16 reported a high incidence of sudden death in Mg-deficient rats, and this result is consistent with epidemiological reports of a high incidence of sudden death in areas with low levels of Mg in drinking water 17 and also with clinical reports that hypomagnesemia is frequently observed in patients with heart failure in whom sudden death occurs. 14,18 Animal studies have suggested that there are 2 mechanisms of sudden death related to Mg deficiency: arrhythmogenesis and coronary vasospasm. 1,4,5,19 Moreover, the effect of Mg deficiency on the autonomic nervous system may act as a neurogenic trigger of a fatal event.…”
mentioning
confidence: 99%
“…Six to sixty-fi ve percent of all hospitalized patients exhibit low serum Mg; patients with numerous cardiovascular disorders associated with atherogenesis demonstrate the most profound defi cits in body Mg. 3,[10][11][12][13][14][15][16][17][18][19][20][21] 22,23 Because the levels of anions can vary signifi cantly in pathological states, and in view of the role apparently played by Mg in cellular homeostasis (Table 19.2), it is desirable to directly measure free Mg 2+ in blood 24 and other body fl uids. With this aim in mind, Mg 2+ -sensitive electrodes have been designed to obtain these measurements in the presence of potential cationic interferences.…”
Section: Magnesium Depletion From the Body Is Commonmentioning
confidence: 99%